رحلة في استكشاف العطور - دانا دراغمة (My University, 2025)
The Perfume Factory Project is more than just a production space; it is a sensory journey that weaves together the relationship between people and nature through fragrance—a delicate element that carries the memory and spirit of a place. The project is located in the area of Solomon’s Pools, south of Bethlehem, where calmness lives between historic reservoirs and gently terraced landscapes. From this natural rhythm, the design found its inspiration, drawing from the layered structure of the three pools and the aromatic pyramid, which also unfolds in three harmonious levels, much like the experiences crafted within this space. I chose this project because perfume is not just a product—it is a memory, a cultural expression, a deeply human experience. Palestine is rich in aromatic plants that deserve to be celebrated and transformed into something meaningful, something that reflects the essence of this land. I imagined a place where visitors feel welcomed, where they are guided through a journey that begins in the earth and ends with a fragrance that lingers in the soul. The project’s value lies in its ability to merge industry with beauty, knowledge with emotion. It includes cultivated fields of aromatic plants, production spaces for extraction, fermentation, and packaging, as well as a shop where perfumes are sold, a café overlooking nature, and a small museum telling the story of fragrance—from soil to bottle. There are also outdoor seating areas scattered among the fields, creating moments of rest and reflection. Visitors do not merely pass through this place—they live an experience. From the very first step, they are greeted by the scent of flowers, guided through paths among plants, and immersed in the visible process of perfume-making. They may even craft their own fragrance. These simple moments carry the joy of discovery and the warmth of nature, sending them home with a memory that is meant to last.